Acnnual inventories of retrogressive thaw slumps across the Qinghai-Tibet Plateau from 2016 t0 2022 - Zhuoxuan, XIA; Liu, Lin; Mu, Cuicui; Peng, Xiaoqing; Zhao, Zhuoyi; Huang, Lingcao; Luo, Jing; Fan, Chengyan (Zenodo, 2024)
The dataset is retrogressive thaw slump inventories with annual intervals across the plateau from 2016 to 2022. It contains the boundaries of thaw slumps delineated yearly based on the PlanetScope Scenes with high resolution (3-5 m). The inventories were compiled semi-automatically by combining deep-learning detection and manual delineation. We assigned a unique ID to every RTS in 2022 and the corresponding polygons in previous years. For RTSs merged into one in 2022, we assigned the same ID to make them traceable. It is the first of this kind to provide annual large-scale thaw slump observations across the QTP and can potentially be a benchmark for monitoring permafrost and evaluating its impact. The vector file in shapefile format contains the boundary of each hot melt collapse. The name of the file is “QTP_RTS_YYYY”, with the ‘YYYY’ representing the year of the boundaries. Relevant attribute tables include unique numbers, with the corresponding names of the table fields Id”.